Ex vivo evaluation of the effectiveness of bleaching agents on the shade alteration of blood-stained teeth - Yui, K. C. K. [UNESP]; Rodrigues, J. R. [UNESP]; Mancini, M. N. G. [UNESP]; Balducci, Ivan [UNESP]; Goncalves, S. E. P. [UNESP] (Wiley-Blackwell, 2008)
Aim To evaluate ex vivo effectiveness of the three formulations of bleaching materials for intracoronal bleaching of root filled teeth using the walking bleach technique.Methodology Extracted premolar teeth were stained artificially with human blood. After biomechanical preparation, the root canals were filled and a 3-mm thick intermediate base of zinc phosphate cement was placed at the level of the cementoenamel junction. The teeth were divided into four groups (n = 12): C (control, without bleaching material), A1 (sodium perborate + distilled water), A2 (sodium perborate + 10% carbamide peroxide) and A3 (sodium perborate + 35% carbamide peroxide). The bleaching materials were changed at 7 and 14 days. Evaluation of shade was undertaken with aid of the VITA Easyshade (TM) (Delta E*ab) and was performed after tooth staining and at 7, 14 and 21 days after bleaching, based on the CIELAB system. Data were analysed by ANOVA for repeated measurements, Tukey and Dunnett tests (alpha = 0.05).Results The Tukey test revealed that group A1 (10.58 +/- 4.83 Delta E*ab) was statistically different from the others (A2, 19.57 +/- 4.72 Delta E*ab and A3, 17.58 +/- 3.33 Delta E*ab), which were not different from each other. At 7 days: A1 was significantly different from A2; at 14 and 21 days: A2 and A3 were significantly better than A1; the Dunnett test revealed that the control group was different from A1, A2 and A3 at all periods (P < 0.05).Conclusion Sodium perborate associated with both 10% and 35% carbamide peroxide was more effective than when associated with distilled water.
Keywords: carbamide peroxide; dental materials; nonvital tooth; shade; sodium perborate; tooth bleaching